Promoting Information Literacy for Science Education Programs: Correlating the National Science Education Content Standards with the Association of College and Research Libraries Information Competency Standards for Higher Education - Jennifer Laherty (Issues in Science and Technology Librarianship)
Librarians who want to collaborate with faculty to incorporate information literacy into science education programs should understand the theories, pedagogies, and standards that serve the academic discipline. Understanding the National Science Education Standards (NSES) is beneficial for librarians seeking to partner with disciplinary faculty because librarians familiar with NSES will understand better the science educators' fields of reference and be equipped with the requisite vocabulary to communicate with science faculty. In this paper I map the commonalities between the NSES and the Association of College and Research Libraries Information Competency Standards for Higher Education and discuss the implications these commonalities have for promoting information literacy for science education programs.